PENGARUH MANAJEMEN ASET DAN STRUKTUR MODAL TERHADAP KINERJA KEUANGAN PERUSAHAAN - Selia Mazid, Viona; Nazar, Shinta Ningtiyas (Publika Citra Media, 2025)
This research aims to determine and obtain empirical evidence regarding the effect of Asset Management and Capital Structure on Company Financial Performance. This type of research is associative quantitative research. This research uses secondary data in the form of annual financial reports. Data in the form of annual financial reports. The population in this study were Food & Beverage Sub-sector Companies listed on the Indonesia Stock Exchange in 2022-2023. The sampling technique in this study using purposive sampling method, obtained 98 companies that were used used as samples of the research. Data analysis techniques in this study using the panel data regression method and data analysis tools in this study using the Eviews software program version 12. The results showed that Asset Management and Capital Structure have an effect on on financial performance. The results showed that Asset Management and Capital Structure have an effect on financial performance. Asset management has a negative effect on financial performance. Capital structure has a negative effect on financial performance.